Haustorium initiation in the obligate parasitic plant Phelipanche ramosa involves a host-exudated cytokinin signal - Goyet, Vincent; Billard, Estelle; Pouvreau, Jean-Bernard; Lechat, Marc-Marie; Pelletier, Sandra; Bahut, Muriel; Monteau, Fabrice; Spíchal, Lukáš; Delavault, Philippe; Montiel, Grégory; Simier, Philippe (Journal of Experimental Botany, 2017)
The heterotrophic lifestyle of parasitic plants relies on the development of the haustorium, a specific infectious organ required for attachment to host roots. While haustorium development is initiated upon chemodetection of host-derived molecules in hemiparasitic plants, the induction of haustorium formation remains largely unknown in holoparasitic species such as Phelipanche ramosa. This work demonstrates that the root exudates of the host plant Brassica napus contain allelochemicals displaying haustorium-inducing activity on P. ramosa germinating seeds, which increases the parasite aggressiveness. A de novo assembled transcriptome and microarray approach with P. ramosa during early haustorium formation upon treatment with B. napus root exudates allowed the identification of differentially expressed genes involved in hormone signaling. Bioassays using exogenous cytokinins and the specific cytokinin receptor inhibitor PI-55 showed that cytokinins induced haustorium formation and increased parasite aggressiveness. Root exudates triggered the expression of cytokinin-responsive genes during early haustorium development in germinated seeds, and bio-guided UPLC-ESI(+)-/MS/MS analysis showed that these exudates contain a cytokinin with dihydrozeatin characteristics. These results suggest that cytokinins constitutively exudated from host roots play a major role in haustorium formation and aggressiveness in P. ramosa.
Keywords: Cytokinins; regulátory růstu rostlin; Brassica napus; Orobanche; Plant Roots; kořeny rostlin; Plant Growth Regulators; cytokininy